Pengaruh Akuntansi Hijau, Kepemilikan Manajerial, dan Kepemilikan Institusional terhadap Nilai Perusahaan (The Influence of Green Accounting, Managerial Ownership, and Institution Ownership on Firm Value) - Sitanggang, Sondang Uli; Hutabarat, Francis M.; Simbolon, Richard Friendly (Akutansi Bisnis & Manajemen ( ABM ), 2024)
This study aims to analyze how company value is affected by green accounting, management ownership, and institutional ownership. To achieve this goal, the population for this study was taken from the reports of companies listed in the Sri Kehati index and sampled by the purposive sampling method. Data was obtained from the annual financial statements of companies in the period 2018 to 2022. This study uses a descriptive research design with the help of SmartPLS software version 3.0. The results of this study show that green accounting has a significant and positive effect on company value, while institutional and managerial ownership has a significant and negative effect on company value.